Praktik Identitas dalam Desain Kemasan Makanan UKM - Moch. Junaidi Hidayat; Faruk HT -; Lono Lastoro Simatupang; Yasraf Amir Pialang (LP2M ISBI Bandung, 2014)
ABSTRACT Small-Medium Scale Business continues to make creative process especially by making serious eﬀort to change the Small-Medium Scale Business image that during this time as the subcultural eco- nomic movement to be the great economic power. One of the eﬀorts is through packaging design. The objective of this research is: a) to know the identity practice of Small – Medium Scale business through packaging design, b) to describe the reposition eﬀort of Small – Medium Scale Business through packag- ing design in economic political practice of packaging design.Through cultural studies approach, this article is the result of research revealing the practice of identity made by Small-Medium Scale Business especially Small-Medium Scale Business of snack as the typical souvenir of Malang Regency, East Java, namely fruit snack. The finding shows practice of identity of Small-Medium Scale Business through packaging design, namely visualization, material up to production pattern of packaging design. Other findings of this research is the eﬀort of Small Medium Scale Business in improving packaging image of its products as the part of reposition of Small-Me- dium Scale Business to win the market competition. In this case, it is realized as the point in economic political practice. Therefore, this research is capable of providing the result of practice of identity made by Small Medium Scale Business through packaging design by means of critical analysis of cultural studies. Keywords: design, packaging, practice of Identity ABSTRAK UKM terus melakukan proses kreatif khususnya berupaya merubah citra UKM yang se- lama ini sebagai gerakan ekonomi subkultur menjadi kekuatan ekonomi yang besar. Salah satu upaya itu dilakukan melalui desain kemasan. Penelitian ini memiliki tujuan: a) mengetahui praktek identitas UKM melalui desain kemasan, b) mendeskripsikan upaya reposisi UKM me- lalui desain kemasan dalam praktek politik ekonomi desain kemasan.Melalui pendekatan etnografi, tulisan ini merupakan hasil penelitian yang mengungkap tentang praktek identitas yang dilakukan oleh UKM khususnya UKM makanan ringan sebagai oleh-oleh khas dari Kabupaten Malang, Jawa Timur yakni keripik buah. Hasil yang sudah di dapatkan adalah praktek identitas UKM melalui desain kemasan yakni visualisasi, material, hingga pola produksi desain kemasan. Penemuan lain dari penelitian ini adalah upaya UKM guna menaikkan citra kemasan hasil produksinya sebagai bagian reposisi UKM sebagai bagian guna memenangkan persaingan pasar. Dimana hal ini disadari sebagai sebuah ujung dalam praktek politik ekonomi. Sehingga, penelitian ini mampu memberikan hasil bagaimana praktek identitas yang dilakukan UKM melalui desain kemasan dengan analisis kritis cultural studies. Kata kunci: desain, kemasan, praktek identitas